Shelby Oaks [videorecording (DVD)] - Stuckmann, Chris; Sam Liz; Burkholder, James; Foley, Shawna-Nova; Baird, Andrew Scott; Sullivan, Camille; Sexton, Brendan, 1980-; David, Keith; Durn, Sarah; Mears, Derek; Bennett, Emily (Actor); Talbert, Charlie; et al. (Decal Releasing, LLC : Neon, 2026)
A film crew uncover a disturbing new lead in a woman's obsessive search for her missing sister, which steers her into a terrifying mystery at the hands of an unknown evil.